A review of sotagliflozin for use in type 1 diabetes. (November 2019) - Nuffer, Wesley; Williams, Briana; Trujillo, Jennifer M.
Type 1 diabetes is a challenging disease that is largely managed with the use of insulin. The risk of hypoglycemia, side effects of weight gain, and high glucose variability associated with insulin use have prompted researchers to explore additional therapies to treat this condition. Sodium-glucose cotransporter 2 (SGLT2) inhibitors are a class of medications that lower glucose in type 2 diabetes patients independent of insulin action, and have been studied for use in the type 1 diabetes population. Sotagliflozin is an SGLT2 inhibitor that demonstrates a unique binding affinity for the SGLT1 receptor. A total of three phase III clinical trials (inTandem1, inTandem2, and inTandem3) were conducted to evaluate the safety and efficacy of sotagliflozin in type 1 diabetes. A modest hemoglobin A1C reduction of 0.3–0.4% was observed, with secondary benefits of reduced glucose variability, reduced insulin dosage, and positive weight loss effects. Overall there was a reduction in the risk of severe hypoglycemia with sotagliflozin, but a higher rate of ketone formation and risk of diabetic ketoacidosis was observed, along with increased mycotic infections and volume depletion effects.